Diagnostic Value of Platelet Index as An Early Marker in Suspected Neonatal Sepsis in The Neonatology Unit - Ferawati Ferawati; Pertin Sianturi; Yazid Dimyati; Arlinda Sari Wahyuni; Ayodhia Pitaloka Pasaribu; Bugis Mardina Lubis (GLOBAL HEALTH SCIENCE GROUP, 2026)
Sepsis neonatorum is a serious blood infection in newborns, mainly affecting premature or low birth weight infants. Early detection is tough, but new research suggests platelet indices could help diagnose it faster. The objective of this study is to analyze the diagnostic value of platelet indices (platelet count, MPV, and PDW) as early markers in suspected neonatal sepsis compared with the gold standard (blood culture). This was an observational analytical study with a retrospective cohort design conducted at the Adam Malik Hospital. A total of 115 suspected neonatal sepsis samples were enrolled. Data collection included demographic characteristics, platelet count, mean platelet volume (MPV), and platelet distribution width (PDW). The data were obtained from secondary sources in medical records and entered into the SPSS software for analysis. Statistical analysis was performed using receiver operator curve (ROC) to assess the diagnostic value of platelet indices (platelet, MPV, and PDW). The study involved 115 newborns suspected of neonatal sepsis, with 46.1% male and 53.9% female. Most were delivered via cesarean section and diagnosed with early onset sepsis. Common clinical signs included respiratory distress and distension. Key risk factors included prolonged rupture of membranes and low birth weight. Blood culture revealed Klebsiella pneumonia as the most common pathogen. Platelet indices showed varied sensitivity and specificity as predictors of sepsis. Diagnostic tests had low sensitivity but varied specificity for detecting sepsis with platelet count, MPV, and PDW.